EKSPERIMENTASI MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) DAN JIGSAW DENGAN PENDEKATAN MATEMATIKA REALISTIK DITINJAU DARI KECEMASAN MENGHADAPI TES SISWA KELAS VII SMP KABUPATEN BREBES TAHUN PELAJARAN 2012/2013 - Budi Santosa; Budiyono Budiyono; Sri Subanti (Jurnal Pembelajaran Matematika, 2014)
ABSTRACT: The objectives of this research were to investigate: (1) which learning model of the TGT type learning model, the Jigsaw type learning model approach, and the direct learning model results in a better learning achievement; (2) which students of those with the high anxiety, those with medium anxiety level, and those with the low anxiety level to deal with test have a better learning achievement in Mathematics; (3) in the students with the low, medium, and high anxiety levels to deal with test, which learning model of the TGT type learning model, the Jigsaw type learning model, and the direct learning results in a better learning achievement in Mathematics; and (4) In the TGT type learning model, the Jigsaw type learning model, and the direct learning model, which students of those with the high anxiety, those with medium anxiety level, and those with the low anxiety level to deal with test have a better learning achievement in Mathematics. This research used the quasi experimental research method with the factorial design of 3 x 3. It was conducted at Class VII of Junior Secondary Schools of Brebes regency in Semester II in Academic Year 2012/2013. The samples of the research were taken by using the stratified cluster random sampling. The data of the research were gathered through multiple choice test and questionnaire anxiety level to deal with test. The data were analyzed by using the two-way analysis of variance with unbalanced cells at the significance level of α = 0.05. The results of the research are as follows: 1) The Jigsaw learning model results in a better learning achievement than both the TGT type learning model and the direct learning model, and the TGT type learning model results in a better learning achievement than the direct learning model. 2) The learning achievement of the students with the low anxiety level is better than those with those with high anxiety level and those with the medium anxiety level, but the learning achievement of the students with the high anxiety level is the same as that of the students with the medium anxiety level. 3) In the students with the high anxiety level to deal with test, the Jigsaw learning model results in a better learning achievement than the TGT learning model. In the students with the medium anxiety level to deal with test, the Jigsaw learning model results in a better learning achievement than the direct learning model. Other than those, in each anxiety level, the three learning models result in the same learning achievement. 4). In the TGT learning model, the learning achievement of the students with the low anxiety level to deal with test is better than that of those with the high anxiety level. Other than those, in each learning model, the students with the high, medium, and low anxiety levels have the same learning achievement in Mathematics.Keywords: Anxiety to deal with test, TGT learning model, Jigsaw, and realistic Mathematics.